Teaching Practicum in Private Schools: Opportunities and Challenges (Journal of Education and Educational Development, 2023)
The success criteria of any program, largely revolves around the success of its graduate in the practical field. The teaching practicum gives such opportunities for the prospective teachers to acquire desired teaching skills for a successful -career. The purpose of this study was to explore the experiences of the prospective teachers during teaching practicum by highlighting the opportunities and challenges. As private schools have been recently added to the pool of schools for practicum, therefore the study was delimited to the practicum in private schools that takes place during the third year of their program. Data was collected from 15 prospective teachers of three batches with help of semi-structured interviews. The data analysis was done through initial coding and then classifying codes into four themes. The emerging themes revealed opportunities in organized environments, infrastructure with facilities, and rigorous learning. Whereas the obstacles included allocation of classes, work pressure and trust concerns of cooperative teachers. However, the challenges didn’t shadow the learning of prospective teachers and served as much needed experience needed to be successful in future. This research aims to assist teacher educators and policymakers in harnessing the full potential of teaching practicum to cultivate a skilled workforce, ultimately enhancing the quality of education.